Thermally Conductive Polyethylene/Expanded Graphite Composites as Heat Transfer Surface: Mechanical, Thermo-Physical and Surface Behavior - Patrik Sobolčiak (4401364) (2020)
Composites of high-density polyethylene (HDPE) and expanded graphite (EG) are prepared for heat exchangers in multi-effect distillation (MED) desalination. At 50 wt.% EG loading, the thermal conductivity of HDPE was increased by 372%. Moreover, the surface wettability of the HDPE/EG composite was enhanced by corona and RF plasma treatment as demonstrated by the increase in surface free energy from 28.5 mJ/m2 for untreated HDPE/EG to 55.5 and 54.5 mJ/m2 for HDPE/EG treated by corona and RF plasma, respectively. This enhanced surface wettability was retained over a long time with only a 9% and 18% decrease in RF and corona plasma-treated samples’ surface energy after two months. The viscoelastic moduli and the complex viscosity profiles indicated that EG content dictates the optimum processing technique. At loading below 30 wt.%, the extrusion process is preferred, while above 30 wt.% loading, injection molding is preferred. The plasma treatment also improved the HDPE/EG composite overall heat transfer coefficient with an overall heat transfer coefficient of the composite reaching about 98% that of stainless steel. Moreover, the plasma-treated composite exhibited superior resistance to crystallization fouling in both CaSO4 solution and artificial seawater compared to untreated composites and stainless-steel surfaces. Other Information Published in: Polymers License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/polym12122863